IASB FRAMEWORK REGARDING THE HARMONIZATION OF FINANCIAL STATEMENTS - NICOLETA-CORNELIA BRAN (STAN) (Annals of the University of Petrosani: Economics, 2011)
Accounting harmonization has imposed on a certain stage of economic and social development, as a practical necessity, seeking coordination based on uniform standards of accounting work. The purpose of this paper is to highlight the importance of general accounting framework for harmonization financial statements aiming to be a starting point for research, without exhausting the subject. The main source of information used to achieve this paper was a preliminary documentation in order to understand theoretical concept regarding the demarcation of the harmonization concept.